Mandatory Infant Vaccinations in France During the COVID-19 Pandemic in 2020 - Taine, Marion; Offredo, Lucile; Drouin, Jérôme; Toubiana, Julie; Weill, Alain; Zureik, Mahmoud; Dray-Spira, Rosemary (Frontiers in Pediatrics, 2021)
Objectives: To describe changes in the dispensation of 11 mandatory vaccines to infants in France during the COVID-19 pandemic in 2020, considering the priming doses and boosters separately. Methods: With data from the French national health database, all dispensations of priming doses and boosters of 11 mandatory vaccines [penta/hexavalent, measles mumps rubella (MMR), meningococcal conjugate type-C (Men-C-C), 13-valent pneumococcal conjugate (PCV13)] for infants ≤24 months old were aggregated by 4-week periods in 2020. Expected counts in 2020 were estimated according to counts in 2019 weighted by a ratio considering the level of vaccine dispensation before the pandemic onset in 2020. Relative differences (RDs) and their 95% confidence intervals (CIs) were computed to compare the observed and expected counts during the first and second lockdown and the period in between. Results: During the first 4 weeks of the first lockdown, as compared with the expected numbers, the observed priming dose counts substantially decreased [RD: from −5.7% (95% CI −6.1; −5.2) for penta/hexavalent to −25.2% (95% CI −25.6; −24.8) for MMR], as did the booster counts [RD: from −15.3% (95% CI −15.9; −14.7) for penta/hexavalent to −20.7% (95% CI −21.3; −20.2) for Men-C-C]. Counts for priming doses and boosters remained slightly below the expected numbers after the lockdown. During 2020, MMR priming doses and the Men-C-C booster had the greatest shortfalls (N = 84,893 and 72,500, respectively). Conclusions: This study provides evidence of a lack of vaccination catch-up after the first lockdown and a persistent shortfall in infant vaccination after the first 10 months of the COVID-19 pandemic in France, especially for the MMR priming doses and Men-C-C booster.